Analisis Strategi Pemasaran Barang Dagang Guna Menciptakan Persaingan pada PT. Cipta Niaga Semesta Medan - Hosanna Lestari Simanjuntak; Henri Saragih; Jon Henri Purba (Jurnal Ilmu Manajemen METHONOMIX, 2024)
This study aims to analyze the merchandise marketing strategy in order to create competition at PT. Cipta Niaga Semesta Medan. This type of research data uses quantitative data. The number of research samples was 91 people. The data collection method used a questionnaire. Methods of data analysis using simple linear regression. The simple linear regression results that produce the following equation: Y = 7,416 + 0.692X + e which means that the better and optimal the marketing strategy set by the company, the more likely it will be to create business competition against similar competitors. The results of the t test found that there was a positive and significant effect of marketing strategy in creating competition. The coefficient of determination which shows the effect of marketing strategies in creating competition is 51%.